Psychosocial risks for post-partum depression among pregnant women in selected health facilities in Kiambu County, Kenya - Kahiga, Keziah W.; Makworo, Drusilla M.; Ndegwa, Stephen N. (International Journal Of Community Medicine And Public Health, 2024)
Background: Post-partum depression (PPD) is an impactful public health problem. Events prior to and in the peripartum period can predispose a pregnant woman to mental deviations in the post-partum period since pregnancy results in major physiological, social and psychological changes. This study sought to assess the psychosocial risks for post-natal depression among pregnant women. Methods: A hospital-based comparative design was employed to collect data from 392 antenatal mothers in two hospitals and were in their first or second trimester, selected using simple random method from the antenatal register. They were assessed for psychosocial risks using the antenatal risk questionnaire. Data analysis was conducted using the SPSS version 29. Results: The mothers were mainly below 18 years (53.1%, 41.5%, p=0.024); had no income or depended on spousal support (54.6%, 51.8%, p=0.618). Prolonged periods of worry which interfered with work or relationships accounted for 54.1% and 56.9% (p=0.027). Partner emotional support was reported by 46.9%, and 48.5% (p=0.000) and they would have support with the baby (47.9%, 43%, p=0.000). There are those who reported to be worriers (75%, 84.2%, p=0.000) and those who become upset when there is no order in their life (81.7%, 80.6%, p=0.000). Most of the participants had not experienced emotional support when growing up (74.5%, 87.2%, p=0.002) nor sexual/physical abuse (84.2%, 96.9%, p=0.000). Marital status and educational level were significantly associated with the total psychosocial risk score (F=3.123; p=0.031, 0.001). Conclusions: psychosocial determinants of PPD include young age, poor source of income and prolonged periods of worry.